Methods and Strategies of Preaching by Ustadz Abdul Somad Through Social Media YouTube - Dedek Syahputra; Indo Santalia; Hamiruddin (Jurnal Mercusuar, 2023)
Methods and Strategies of Da’wah by Ustadz Abdul Somad Through the Social Media YouTube. The objective of this research is to describe and analyze the methods and strategies of da’wah used by Ustadz Abdul Somad, a preacher originating from the Riau Province. The research scope includes the Al-Hikmah da’wah method employed by Ustadz Abdul Somad on YouTube and the da’wah strategies applied by Ustadz Abdul Somad on YouTube. The research type utilized is descriptive, with the research approach being a combination of da’wah and communication approaches, specifically da’wah and ethnography with a predominant focus on qualitative methods. Additionally, this research is categorized as "Library Research" (literature-based), drawing from various literature sources, including Ustadz Abdul Somad’s own works. The findings of this research indicate that Ustadz Abdul Somad employs three methods: Al-Hikmah, wherein Ustadz Abdul Somad, as a preacher, sets an example first; Al-Mauidzah Al-Hasanah, where Ustadz Abdul Somad consistently advocates for doing good to everyone; and Al-Mujadalah Al-Ahsan, utilized by Ustadz Abdul Somad in discussions and Q&A sessions, focusing on the sciences of fiqh and Al-Hadith, supported by numerous memorized hadiths with clear chains of narration and their contextual reasons. The strategies employed by Ustadz Abdul Somad involve a rational approach (Aq’li methodology) and tactical techniques utilizing YouTube, Instagram, and Facebook. The implication of this research is that further studies on da’wah on YouTube in Indonesia are encouraged. This can bring new perspectives to understanding da’wah through increasingly sophisticated social media, which presents both positive and negative aspects for the younger generation in Indonesia.